2022
DOI: 10.18174/sesmo.18127
|View full text |Cite
|
Sign up to set email alerts
|

18 Politically relevant solar geoengineering scenarios

Abstract: Solar geoengineering, also known as Solar Radiation Modification (SRM), has been proposed to alter Earth’s radiative balance to reduce the effects of anthropogenic climate change. SRM has been identified as a research priority, as it has been shown to effectively reduce surface temperatures, while substantial uncertainties remain around side effects and impacts. Global modeling studies of SRM have often relied on idealized scenarios to understand the physical processes of interventions and their widespread imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 166 publications
0
7
0
Order By: Relevance
“…In this study, we examine as SRM as an emergency intervention instead, to be deployed only after prolonged heating. This notion, adapted from Lockley et al (2022), naturally arises when SRM deployments are restricted to particularly extreme situations such as rapid climate tipping. To what extent can later deployments reverse the impacts of heating?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we examine as SRM as an emergency intervention instead, to be deployed only after prolonged heating. This notion, adapted from Lockley et al (2022), naturally arises when SRM deployments are restricted to particularly extreme situations such as rapid climate tipping. To what extent can later deployments reverse the impacts of heating?…”
Section: Introductionmentioning
confidence: 99%
“…This notion, adapted from Lockley et al. (2022), naturally arises when SRM deployments are restricted to particularly extreme situations such as rapid climate tipping. To what extent can later deployments reverse the impacts of heating?…”
Section: Introductionmentioning
confidence: 99%
“…There are many uncertainties associated with this intervention, including risks to the stratospheric ozone layer that could increase ground-level UV irradiance [ 23 25 ]. In addition to the risks associated with the initiation of SAI, once adopted, any subsequent termination of this climate intervention would lead to a rapid increase in temperature and extreme deleterious effects on ecosystems [ 26 , 27 ]. This, and other SRM interventions, would likely expose the Earth’s ecosystems to new and potentially rapidly changing combinations of UV radiation and other biotic and abiotic environmental factors [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several Earth‐system models have been used to simulate a future climate with SAI under different climate change scenarios (Kravitz et al., 2011; Richter et al., 2022; Tilmes et al., 2018; Visioni et al., 2023). Research to date has included examining changes in global and regional temperature and precipitation (Hueholt et al., 2023; Richter et al., 2022; Tilmes et al., 2018), atmospheric circulation patterns (Bednarz et al., 2022), extreme temperature and precipitation events (Barnes et al., 2022; Ji et al., 2018), and ecological responses (Zarnetske et al., 2021), in addition to potential deployment technologies (Lockley et al., 2022; Smith & Wagner, 2018). Such studies have demonstrated that SAI could potentially be deployed to stabilize or reduce global mean temperature to a specific temperature target (Richter et al., 2022; Tilmes et al., 2018; Visioni et al., 2021); however, research has also indicated that regional impacts of SAI could be both positive and negative compared to the impacts and risks of anthropogenic climate change.…”
Section: Introductionmentioning
confidence: 99%